Inhalation drug delivery : techniques and products - Colombo, Paolo, 1944-; Traini, Daniela; Buttini, Francesca (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2013)
"Provides students and those in industry with concise clear guide to the essential fundamentals in inhalation drug delivery"--Provided by publisher.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on Mar. 25, 2013).
Keywords: Aerosol therapy; Inhalers; Respiratory therapy; Pharmaceutical technology; Administration, Inhalation; Drug Delivery Systems -- methods; Aerosol therapy; Inhalers; Pharmaceutical technology; Respiratory therapy; Australian; Electronic books